Life assessment of power transformer via furans analysis - Poniran, Zalizah (2006)
The status of insulation in electrical power equipment at any given point in time can be assessed by monitoring several properties which are sensitive to the amount of ageing. This procedure is commonly known as the diagnostic or non-destructive testing. For power transformers, the condition of the paper insulation can be assessed by an examination of the tracks provided by by-products of chemical dissociation of cellulose in solution with oil. This work addresses the need of paper insulation condition monitoring by determining the furfural contents in transformer oil using High Performance Liquid Chromatography (HPLC) technique. The degradation of electrical Kraft paper under laboratory ageing experiment was examined by means of assessing the increase of concentration of furan compounds as well as the increase of moisture content. Experimental results show that the thermal ageing process causes a proportional increase in 2-FAL furan compound as well as in moisture content. Both increases were shown to be related to the ageing or degradation of paper insulation.